PENGARUH KUALITAS PELAYANAN DRIVER OJEK ONLINE TERHADAP KEPUASAN PELANGGAN PADA PT GO-JEK INDONESIA DI SAMARINDA - Sattar, Sattar (PT Kimshafi Alung Cipta, 2022)
This study aims to determine the effect of partially and simultaneously the level of work discipline and work environment on the performance of employees of PT Bhakti Karya Distribution Indonesia. The benefits of this research for the company as input in managing performance by using work discipline and work environment on employee performance and as consideration for determining the next steps in the employee performance system in the future. The research method used is quantitative associative data, in the form of employees of PT. Bhakti Karya Distribution Indonesia. While the population in this study were all employees of PT. Bhakti Karya Distribution Indonesia, totaling 87 people. The sampling technique in this study uses saturated sampling, it is said to be saturated sample because all members of the population are used as samples. This research uses Instrument Test, Classical Assumption Test. Analysis to see the effect of variables using Linear Regression Analysis, Correlation Analysis, Coefficient of Determination Test and Partial Hypothesis Testing (T Test) and Simultaneous Hypothesis Testing (F Test). The results of this study indicate that partially (T-test) work discipline has a positive effect on employee performance, as evidenced by the results of the calculation of work discipline having a value with a significant probability of 0.002 which is smaller than the predetermined significant level of 0.05, thus Ho is rejected. and Ha accepted. Partially the work environment variable has a positive effect on employee performance, as evidenced by the results of the work environment having a value of 0.002 which is smaller than the predetermined significant level of 0.05, thus Ho is rejected and Ha is accepted. The Fcount value obtained is 12.606 and the Ftable value is 3.11. So that Fcount > Ftable with a significant probability level of 0.002, which is smaller than the predetermined significant level of 0.05. Thus, Ho is rejected and Ha is accepted so that it can be concluded that there is a significant influence between work discipline and work environment simultaneously on employee performance.